Reproducibility of rapid multi‐parameter mapping at 3T and 7T with highly segmented and accelerated 3D‐EPI - Wang, Difei; Ehses, Philipp; Stöcker, Tony; Stirnberg, Rüdiger (Magnetic resonance in medicine, 2022)
Purpose Quantitative multi‐parameter mapping (MPM) has been shown to provide good longitudinal and cross‐sectional reproducibility for clinical research. Unfortunately, acquisition times (TAs) are typically infeasible for routine scanning at high resolutions. Methods A fast whole‐brain MPM protocol based on interleaved multi‐shot 3D‐EPI with controlled aliasing (SC‐EPI) at 3T and 7T is proposed and compared with MPM using a standard spoiled gradient echo (FLASH) sequence. Four parameters (R1, PD, R2*$$ R_2^{* } $$, and MTsat) were measured in less than 3 min at 1 mm isotropic resolution. Five subjects went through the same scanning sessions twice at each scanner. The intra‐subject coefficient of variation (scan–rescan) (CoV) was estimated for each protocol and scanner to assess the longitudinal reproducibility. Results At 3T, the CoV of SC‐EPI ranged between 1.2%–4.8% for PD and R1, 2.8%–10.6% for R2*$$ R_2^{* } $$ and MTsat, which was comparable with FLASH (0.6%–4.9% for PD and R1, 2.6%–11.3% for R2*$$ R_2^{* } $$ and MTsat). At 7T, where the SC‐EPI TA was reduced to ∼2 min, the CoV of SC‐EPI (1.4%–10.6% for PD, R1, and R2*$$ R_2^{* } $$) was 1.2–2.4 times larger than the CoV of FLASH (1.0%–15%) and MTsat showed much higher variability across subjects. The SC‐EPI‐MPM protocol at 3T showed high reproducibility and yielded stable quantitative maps at a clinically feasible resolution and scan time, whereas at 7T, MT saturation homogeneity needs to be improved. Conclusion SC‐EPI‐based MPM is feasible as an additional MRI modality in clinical or population studies where the parameters offer great potential as biomarkers.